Influence of Spatially Varying Flow on the Dynamic Response of a Waterjet inside an SES - Michael R. Motley; Brant R. Savander; Yin L. Young (International Journal of Rotating Machinery)
Surface Effect Ships (SES) are a promising fuel-efficient ship technology that typically carry most of their weight on an air cushion. To accommodate its shallow draft and slender side hulls and to absorb the high thrust and power required for high-speed applications, waterjets are typically used as the primary propulsion system. A waterjet typically has a flush mounted inlet and operates under complex three-dimensional flow conditions that result in highly nonuniform flows. The objectives of this work are to quantify the flow nonuniformity and the influence of unsteady cavitation on the response of an SES-waterjet system and to investigate the effect of flow nonuniformity and cavitation on the dynamic hydroelastic response of the rotor and stator blades. The results showed that as the flow advances through the pump, the ingested boundary layer from the bottom of the side hulls becomes increasingly nonuniform, particularly between the rotor and stator. The flow nonuniformity was shown to result in hydrodynamic load fluctuations and high side forces on the rotor and stator blades. The unbalanced blade loads lead to the generation of net upward forces on the pump casing and shaft. Flow nonuniformity also leads to unsteady cavitation and unsteady blade stresses and deformations.